PENGARUH JENJANG PENDIDIKAN TERAKHIR, STATUS PEKERJAAN, SERTA PENDAPATAN KELUARGA TERHADAP PARTISIPASI PENGGUNAAN ALAT KONTRASEPSI DI KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Ayu Novita, Hutapea Novita Putri; Lapeti, Sari; Hilmah, Zuryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to see how the influence of the latest level of education, employment status, and family income towards participation in the use of contraceptives in the Payung Sekaki District of Pekanbaru City. The data used are primary data obtained directly from 99 respondents of women of childbearing age in Payung Sekaki District. The analytical method used is multiple logistic binary methods using the statistical program SPSS 24.0. The results obtained that the last level of education as (X1), employment status as (X2), and family income as (X3), and participation in the use of contraceptives as (Y) are considered to have a simultaneous effect on participation in the use of contraceptives in Payung Sekaki District in Pekanbaru City.Keywords: Participation, Latest Education Level, Employment Status, Family Income